Can Leprosy Reaction States Mimic Symptoms of Fibromyalgia? A Cross-Sectional Analytical Study - Maria Stella Cochrane Feitosa; Gabriela Profírio Jardim Santos; Selma Regina Penha Silva Cerqueira; Gabriel Lima Rodrigues; Licia Maria Henrique da Mota; Licia Maria Henrique da Mota; Ciro Martins Gomes; Ciro Martins Gomes; Ciro Martins Gomes (Frontiers in Medicine, 2022)
Leprosy causes significant pain in affected patients, especially those experiencing reactional states. Fibromyalgia is characterized by widespread pain and is often accompanied by fatigue. Confusion between the clinical manifestations of fibromyalgia and those of leprosy reactions is possible at the primary care level, the first contact with the health system in most cases. We aimed to determine whether the presence of leprosy reactional states is related to the development of signs and symptoms included in the case definition of fibromyalgia and establish recommendations for obtaining the correct diagnosis. We performed a cross-sectional study in which the main independent variable was the presence of any leprosy reactional state and the primary dependent variable was the diagnosis of fibromyalgia according to the 2016 Revisions of the 2010/2011Fibromyalgia Provisional Criteria of the American College of Rheumatology. Forty-three patients were included in the study. Twenty-eight (65.12%) patients had a type I reactional state, only 1 (2.33%) had an isolated type II reactional state, and 5 (11.63%) had both type I and type II reactional states. Only 2 patients who suffered from cooccurring type I and II reactional states obtained sufficient scores for the diagnosis of fibromyalgia. Although diffuse pain was common in leprosy patients, none of the types of reactional states were associated with a higher frequency of criteria for fibromyalgia. We can conclude that a leprosy reactional state is probably not a risk factor for fibromyalgia but can act as a confounder, as tender points may be similar in both diagnoses. In patients diagnosed with fibromyalgia, leprosy must be considered in the differential diagnosis in endemic regions.